A multi-group dragonfly algorithm for application in wireless sensor network deployment problem. (25th August 2021) - Wang, Xiaopeng; Chu, Shu-Chuan; Chao, Han-Chieh; Pan, Jeng-Shyang
Metaheuristic algorithm is a popular research field. In recent years, a host of optimisers have been presented. Dragonfly algorithm (DA) mimicking the behaviour of a dragonfly performs markedly competitive to some optimisation problems. However, the DA sometimes does not perform well when encountering some complicated problems, easily falls into the local optimum, and premature convergence. To overcome the deficiencies of the canonical DA, this paper presents an enhanced version of DA, namely the multi-group dragonfly algorithm (MDA). The proposed MDA with three communication strategies applies effectively the multi-group trick to improve the diversity of the population. To verify the performance of the proposed MDA, it is evaluated by different benchmarks including unimodal functions, multimodal functions, hybrid, and composed functions. The experimental data confirm that the MDA performs better than the DA. Besides, the MDA is also applied in the wireless sensor network deployment problem, the simulation results appear that the MDA can obtain a more ideal sensor node distribution.